THE USE OF ECONOMIC TERMS IN MUQIMI'S WORKS - Mukhitdinova Mukhlisa Sadritdinova (Galaxy International Interdisciplinary Research Journal, 2023)
This article talks about the life path, creativity, works and economic views of Muhammad Aminkhoja Muqimi, a great thinker and great statesman who lived in the late 19th and early 20th centuries and created under the pseudonym "Muqimi". In his works, Muhammad Aminkhoja Muqimi clearly described the economic and political situations that occurred in our society in the 19th-20th centuries, and in his works, the main emphasis was on the injustices of the state leaders and officials of that time, and the oppression of the common people.